The Macroeconomics of the Circular Economy Transition A Critical Review of Modelling Approaches - McCarthy, Andrew (OECD Publishing, 2018)
This paper reviews the existing literature on modelling the macroeconomic consequences of the transition to a circular economy. It provides insights into the current state of the art on modelling policies to improve resource efficiency and the transition to a circular economy by examining 24 modelling-based assessments of a circular economy transition
Keywords: Environment